Peranan persepsi kualitas layanan sebagai prediktor niat rekomendasi - Kasereka Majaribu Emmanuel; V. J. Wisnu Wardhono (Universitas Kristen Maranatha, 2024)
Service quality is very important, especially for companies operating in the service sector. Service quality applies to all types of services, including services provided by non-profit organizations. Pratista Retreat House is a religious institution that provides spiritual services through retreats to people who need them. Over the last two years, the Pratista Retreat House has experienced a decline in the number of retreats. Results from previous interviews showed that participants had negative perceptions about service quality. So, this research was conducted to determine the influence of five service quality dimensions on the intention to recommend Pratista services. This research is explanatory with a quantitative approach using surveys to obtain data. The questionnaires distributed to 102 respondents were collected using non-probabilistic sampling techniques in the purposive sampling type. Data processing was carried out using descriptive statistics which showed that 95% of the respondents intended to recommend Pratista services. Then the data was processed using SEM-PLS 4. The results showed that the tangible and the responsiveness positively affected the intention to recommend Pratista Retreat House. In this way, Pratista management can maintain service quality, especially through aspects of physical evidence of service and by being more responsive in handling retreat participants.